2012
DOI: 10.1063/1.4759139
|View full text |Cite
|
Sign up to set email alerts
|

An accurate characterization of interface-state by deep-level transient spectroscopy for Ge metal-insulator-semiconductor capacitors with SiO2/GeO2 bilayer passivation

Abstract: Articles you may be interested inInterface trap characterization of atomic layer deposition Al2O3/GaN metal-insulator-semiconductor capacitors using optically and thermally based deep level spectroscopies A deep-level transient spectroscopy study of silicon interface states using different silicon nitride surface passivation schemes Appl. Phys. Lett. 96, 103507 (2010); 10.1063/1.3358140 Importance of minority carrier response in accurate characterization of Ge metal-insulator-semiconductor interface traps

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…The Hall effect measurements revealed that the electrical conduction exhibited was entirely p-type owing to the acceptor defects in Ge 20 27 . Figure 3 a shows that p considerably depended on T d , as the behavior of p was strongly related to the density of the HAGBs (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The Hall effect measurements revealed that the electrical conduction exhibited was entirely p-type owing to the acceptor defects in Ge 20 27 . Figure 3 a shows that p considerably depended on T d , as the behavior of p was strongly related to the density of the HAGBs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the above results, we phenomenologically discuss the origin of the acceptor defects in polycrystalline Ge. According to the previous studies, the physical origin of acceptors in Ge was speculated to be vacancies and dangling bonds 19 27 . The correlation between the HAGBs (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The value of the assumed capture cross-section is unfortunately seldom stated in papers. We speculate that a capture cross-section (σ p ) of unstrained Ge is used (typically in order of ∼1 × 10 –15 to 2 × 10 –17 cm 2 ) Therefore, in this work, we use another well-established technique known as Deep Level Transient Spectroscopy (DLTS), to reliably extract the D it .…”
mentioning
confidence: 99%